VOLCANIC HAZARDS IN NICARAGUA: PAST, PRESENT, AND FUTURE - Freundt A.; Kutterolf S.; Schmincke H.-U.; Hansteen T.; Wehrmann H.; Pérez W.; Strauch W.; Navarro M. (My University, 2006)
We review the most important types of volcanic hazards that have occurred in Nicaragua during the past ̃40,000 yr and that are expected to occur in the future. Population density within the potential hazard area is clearly essential in defi ning and understanding volcanic hazard and risk. There are three main groups of volcanic events that pose major hazards: Group 1 comprises several types of explosive volcanic eruptions that impact society (people and infrastructure) directly. The most hazardous types are pyroclastic surges, particularly those generated by water-magma interaction, pyroclastic fallout, and pyroclastic fl ows, as well as tsunamis generated by volcanic eruptions within and close to Nicaragua's large lakes. Group 2 includes nonexplosive volcanic activity such as lava fl ows and the permanent or episodic emission of volcanic gases from open vents. Group 3 comprises chiefl y lahars generated by mixing of volcanic debris with water and volcano fl ank collapses (landslides) sometimes unrelated to synchronous volcanic eruptions but being conditioned chiefl y by the stability of a volcanic edifi ce. We discuss the present database on the age and type of the most recent eruptions emphasizing those that potentially pose major hazards to the populated areas. These include volcanogenic tsunamis in Lake Managua and Lake Nicaragua, scoria cone and maar formation chiefl y in the western part of Managua, and major explosive eruptions of Chiltepe and Masaya volcanoes, a large eruption from Masaya volcano having devastated the entire area of present Managua only ̃2000 yr ago. We discuss the most important techniques for monitoring volcanoes to detect unrest and predict the time and magnitude of upcoming eruptions, emphasizing techniques presently employed in Nicaragua. Finally, we address the subjects of risk assessment, including hazard and risk maps, and the importance of long-term development plans to reduce vulnerability. © 2006 Geological Society of America.
Keywords: DEBRIS FL OWS; ERUPTION FORECASTING; MONITORING; TEPHROSTRATIGRAPHY; TSUNAMIS